2017
DOI: 10.1002/eqe.3011
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced base isolation system equipped with optimal tuned mass damper inerter (TMDI)

Abstract: Summary In seismic base isolation, most of the earthquake‐induced displacement demand is concentrated at the isolation level, thereby the base‐isolation system undergoes large displacements. In an attempt to reduce such displacement demand, this paper proposes an enhanced base‐isolation system incorporating the inerter, a 2‐terminal flywheel device whose generated force is proportional to the relative acceleration between its terminals. The inerter acts as an additional, apparent mass that can be even 200 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
188
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 350 publications
(197 citation statements)
references
References 38 publications
7
188
0
2
Order By: Relevance
“…Inerter is a two-terminal device with the property that the force applied at its two terminals is proportional to the relative acceleration between them, 2 with the constant proportionality named as the inertance in the unit of mass (eg, kilogram). [10][11][12][13][14] Pradono et al 10 investigated the effectiveness of application of inerter to BIS. [3][4][5] Inspired by the successful application of inerters in mechanical engineering, the structural engineering community is now engaged in applying inerters to vibration control of buildings subjected to seismic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…Inerter is a two-terminal device with the property that the force applied at its two terminals is proportional to the relative acceleration between them, 2 with the constant proportionality named as the inertance in the unit of mass (eg, kilogram). [10][11][12][13][14] Pradono et al 10 investigated the effectiveness of application of inerter to BIS. [3][4][5] Inspired by the successful application of inerters in mechanical engineering, the structural engineering community is now engaged in applying inerters to vibration control of buildings subjected to seismic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hessabi et al concluded that the effectiveness of the TMDs in base‐isolated structures with nonlinear base isolation systems is not as significant as for the linear base isolation systems. De Domenico and Ricciardi and De Domenico et al were mainly focused on the possibility of enhancing the effectiveness of the TMD by adding additional rotational inertia via the inerter configuration for response control of isolated buildings.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that by attaching a TMD to the BIS, a certain reduction of the displacement demand of a base-isolated structure is achieved, depending on the TMD mass. Conversely, applications of inerter-based devices in the context of base-isolated structures are really few [21][22][23][24][25]. To the authors' best knowledge, the dynamic layout of the BIS coupled with the TMDI has never been studied in the literature as a seismic retro tting strategy of existing structures, which constitutes the main novelty of the present research work.…”
Section: Base Isolation With Supplemental Rotationalmentioning
confidence: 99%